Signalling indicator of sustainability financial performance in the travel, leisure, and hospitality service industry / Wong Vui Ken & Saizal Pinjaman - Wong, Vui Ken; Pinjaman, Saizal (Universiti Teknologi MARA Cawangan Sarawak, 2022)
This study sought to determine the signal indicator of fundamental and macroeconomic factors on the stock price in Malaysia. The study used dynamic panel data analysis of the system Generalized Method of Moments for 23 listed companies in the Travel, Leisure, and Hospitality industry. The study covered the period from 2013 to 2019. Asymmetric information existed due to the law of supply and demand holding true, leading investors to have different perceptions of the fundamental and macroeconomic factors and stepping forward in decision-making. Inconclusive results regarding both factors limited the industry to determine the main signal indicator. The findings indicate that investors have a different awareness of the performance of the previous year's stock price, operating cash flow, and inflation rate. The yearly performance of operating cash flow could be emphasized to encourage existing or potential investors to remain with the invested companies. This is because the current stock price may positively affect the following year's performance.